Endodontic approach in a replanted tooth with an immature root apex and chronic apical periodontitis: a case report - Graziela Garrido Mori; Bruna Souza Andrade; Marina Bardelli Araujo (Restorative Dentistry & Endodontics, 2020)
This study describes the clinical steps taken in the treatment of a patient who had an avulsed right upper central incisor that presented with incomplete root development and chronic apical periodontitis. A 7-year-old boy was referred from a private dentist to a dental office specializing in endodontics. The tooth had remained in a dry environment for 20 minutes, and tooth replantation was performed at an emergency appointment. After clinical and radiographic examinations, root canal decontamination was performed, followed by several changes in intracanal calcium hydroxide medication. Blood clot formation was attempted, but bleeding within the root canal was insufficient; therefore, we opted for an intracanal medication change to stimulate mineralized tissue formation in the apical region. Root obturation was performed 45 days after the last change of intracanal medication, and clinical, radiographic, and tomographic follow-up examinations were performed at 3, 6, 18, and 40 months after the endodontic intervention. The increase in thickness and length of the root structure and the absence of root resorption were verified through follow-up examinations. Therefore, it was concluded that the procedures used were successful for tooth replantation.